2018
DOI: 10.18267/j.aip.111
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Social Media Data for Recruiting Purposes

Abstract: Social media networks are tools that recruiters can utilize during a recruitment process. Most importantly, social media networks can be used in conjunction with applications capable of downloading information about their potential candidates. The aim of this article is to present a creation process of a model that could be helpful in recruiting area. A crucial part of this model is application software that downloads user's data, particularly from Facebook profiles. This model should propose appropriate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research on climatology has been conducted also by applying CRISP-DM and KDD as a combination to improve the data mining result [32]. Another research on social media analysis has shown a result that CRISP-DM made the data mining processes gave a better result to perform the favorite TV series classification by applying the Decision Tree algorithm [36].…”
Section: Data Mining Methodologymentioning
confidence: 99%
“…Research on climatology has been conducted also by applying CRISP-DM and KDD as a combination to improve the data mining result [32]. Another research on social media analysis has shown a result that CRISP-DM made the data mining processes gave a better result to perform the favorite TV series classification by applying the Decision Tree algorithm [36].…”
Section: Data Mining Methodologymentioning
confidence: 99%
“…As Böhmová and Chudán (2018) point out, in recruitment social media networks offer a solution that is innovative and potentially cost-effective. Social media networks are a virtual space with a huge potential as it is a space where people voluntarily share personal information, which can be used as a way to contact them (Böhmová & Chudán, 2018). People using social media in recruitment need to have social media awareness including the knowledge of how to use and analyse the data they get, and to understand the principles of social media network and communication.…”
Section: Merits and Demerits Of Technologies In Hrmentioning
confidence: 99%